An efficient and low-cost compensation method for exposure uniformity based on digital oblique scanning lithography. (1st July 2022) - Huang, Shengzhou; Jiang, Chengwei; Xie, Fanglin; Sun, Jiale; Li, Mujun; Gao, Qingzhen
Abstract: We proposed an efficient and low-cost compensation method for improving exposure uniformity. A flexible designed uniformity grayscale template compensation strategy based on digital micromirror device oblique scanning lithography was developed, which can effectively improve exposure region uniformity. In order to avoid the asynchronous error of the exposure process, the light-source synchronization control based on the pulse width modulation strategy was introduced in the lithography system. The experimental results showed that the maximum dimensional difference is decreased from 20.7% to 3.3% by the above strategy. The presented method will have a broad application prospect in the printed circuit board manufacturing field.